2009
DOI: 10.1159/000265113
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Aspects of Ménière’s Disease on the Basis of Clinical and Experimental Studies

Abstract: Conclusions: Endolymph homeostasis is thought to be mediated by the vasopressin-aquaporin-2 (VP-AQP2) system in the inner ear. Endolymphatic hydrops, the morphological characteristics of Ménière’s disease (MD), seems to reflect the malregulation of the VP-AQP2 system in inner ear fluid. The elevation of plasma vasopressin (p-VP) level, which is often observed in MD and its related diseases, might be one of the causative factors underlying these diseases. Purpose of Review: Review of the role of the VP-AQP2 sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 68 publications
1
35
0
Order By: Relevance
“…Vasopressin is believed to play an important role in inner ear pathophysiology in humans as well as animals [Takeda et al, 2009[Takeda et al, , 2010. The effects of vasopressin on inner ear fluid homeostasis is mediated by the vasopressin 2 receptor which, via effects on cAMP/Protein kinase A, lead to translocation of aquaporin 2 to the plasma membrane [Sawada et al, 2002, Takeda et al, 2003.…”
Section: Discussionmentioning
confidence: 99%
“…Vasopressin is believed to play an important role in inner ear pathophysiology in humans as well as animals [Takeda et al, 2009[Takeda et al, , 2010. The effects of vasopressin on inner ear fluid homeostasis is mediated by the vasopressin 2 receptor which, via effects on cAMP/Protein kinase A, lead to translocation of aquaporin 2 to the plasma membrane [Sawada et al, 2002, Takeda et al, 2003.…”
Section: Discussionmentioning
confidence: 99%
“…In situ hybridization experiments demonstrated that V2R was expressed throughout the neonatal rat cochlea, whereas none was detected in the adult cochlea (119). On the other hand, chronic application of AVP reduced V2R mRNA expression in the adult rat cochlea (113). This phenomenon can, in many ways, be compared with the so-called "vasopressin escape" that, under certain conditions, allows free water excretion despite inappropriate secretion of vasopressin (124).…”
Section: Distribution and Function Of V2rsmentioning
confidence: 97%
“…In addition all subjects were given a tinnitus questionnaire consisting of 40 multiple choice questions to define the impact of symptoms on the patient life. In the group of patients with diagnosis of Ménière's disease, the grade of severity for each patient (Table 1) was established on the basis of the vertigo attack frequency over a year (from 2 to 8 crisis), the intensity and the duration of symptoms (from a few days, to some weeks, to a month in the most severe case) [17,18]. In this study group, the hearing loss degree was assessed instrumentally allowing staging of the disease in MD patients, as reported in Table 2.…”
Section: Patientsmentioning
confidence: 99%